Surveying shrimp aquaculture pond activity using multitemporal VHSR satellite images - case study from the Perancak estuary, Bali, Indonesia. (June 2018) - Gusmawati, Niken; Soulard, Benoît; Selmaoui-Folcher, Nazha; Proisy, Christophe; Mustafa, Akhmad; Le Gendre, Romain; Laugier, Thierry; Lemonnier, Hugues
Abstract: From the 1980's, Indonesian shrimp production has continuously increased through a large expansion of cultured areas and an intensification of the production. As consequences of diseases and environmental degradations linked to this development, there are currently 250, 000 ha of abandoned ponds in Indonesia. To implement effective procedure to undertake appropriate aquaculture ecosystem assessment and monitoring, an integrated indicator based on four criteria using very high spatial optical satellite images, has been developed to discriminate active from abandoned ponds. These criteria were: presence of water, aerator, feeding bridge and vegetation. This indicator has then been applied to the Perancak estuary, a production area in decline, to highlight the abandonment dynamic between 2001 and 2015. Two risk factors that could contribute to explain dynamics of abandonment were identified: climate conditions and pond locations within the estuary, suggesting that a spatial approach should be integrated in planning processes to operationalize pond rehabilitation. Highlights: An integrated indicator was developed to survey shrimp ponds activity. This tool was developed using VHR satellite images. This indicator was tested to survey an aquaculture area in decline (2001–2015). Climate conditions explain the dynamics of pond abandonment. Findings indicate the need to consider spatial aspects to analyze the dynamic of pond abandonment.